Strategi Desain Kemasan Dalam Membangun Identitas Visual Produk Olahan Pepaya KWT Mandiri Desa Air Satan - Eli Suryani; Kiki Fitaloka; Fahri Saputra; Restu (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Processed papaya products produced by KWT Mandiri in Air Satan Village have economic potential to be developed, but they are not yet supported by packaging design that strongly represents the product’s visual identity. This condition causes limited product attractiveness, brand recognition, and market competitiveness. Therefore, it is necessary to design packaging that not only functions as product protection, but also as a visual communication medium capable of building image and increasing consumer purchase interest. This study aims to develop packaging design that is aesthetic, communicative, and relevant to the characteristics of KWT Mandiri as a local producer, so that it can strengthen product identity and increase its selling value. The method used is a qualitative approach with Tim Brown’s Design Thinking model, which includes the stages of empathize, define, ideate, prototype, and testing. Data were collected through interviews, observation, and visual documentation. The results show that the design process produced a packaging concept that is in accordance with product characteristics and user needs through the development of several design alternatives and evaluation with KWT members. The selected design is considered more capable of presenting local identity, increasing visual attractiveness, and strengthening product image in the market. Thus, packaging design can be a strategic solution in supporting the development and sustainability of KWT Mandiri’s processed papaya business